Osteosarcoma in neonate with rare liver metastasis and abdominal lymphadenopathy - Mohamad Sani, Suraini; Abdul Rahim, Ezamin; Ab Hamid, Suzana; Abu Hasan, Hasyma; Tok, Roger Chung Hong (Community Health Society Malaysia, 2018)
In this study, we report an extremely rare case of osteosarcoma in neonate with rarely metastasis and abdominal lymphadenopathy. The patient appeared to have progressive swelling of the distal right femur. Magnetic Resonance Imaging (MRI) of the right thigh revealed an eccentric lesion arising from the right femur. Computed Tomography (CT) of the thorax and abdomen showed liver metastasis and abdominal lymphadenopathy without lung involvement. It was confirmed to be osteosarcoma with focal rhabdoid features on histopatholigical examination.